2018
DOI: 10.1002/hyp.11625
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrogeomorphic setting on calcareous fen hydrology

Abstract: Calcareous fens are species-rich peatlands that are dependent on minerotrophic water sources for wetland functioning, with current conceptual models suggesting the water source is ubiquitously groundwater upwelling. By quantifying the water balance and subsurface water flow paths and fluxes over 3 growing seasons for calcareous fens in 3 different hydrogeomorphic settings (Riparian, Trough, and Basin), we show evidence that challenges this conceptual model. The Riparian Fen received an order of magnitude more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…Carlson-Mazur et al (2013) reported a linear decrease in Sy to 3 m depth, whereas Bourgault et al (2016Bourgault et al ( & 2018 reported a logarithmic decrease in Sy until 1m depth. Duval & Waddington (2018) found one well location which followed a pattern similar to the Sy increase at depth observed in this study. However, they did not state a cause for the increase in Sy at depth.…”
Section: Specific Yield and Depthsupporting
confidence: 83%
See 1 more Smart Citation
“…Carlson-Mazur et al (2013) reported a linear decrease in Sy to 3 m depth, whereas Bourgault et al (2016Bourgault et al ( & 2018 reported a logarithmic decrease in Sy until 1m depth. Duval & Waddington (2018) found one well location which followed a pattern similar to the Sy increase at depth observed in this study. However, they did not state a cause for the increase in Sy at depth.…”
Section: Specific Yield and Depthsupporting
confidence: 83%
“…The inclusion of mineral sediment within the peat profile changes the soil hydrologic properties (Duval & Waddington, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Calcareous spring‐fed fens (extremely rich fens, sensu Sjörs, ) are globally rare and of great interest to conservationists in Europe and North America because they harbor many endangered plant species (Amon et al., ; Nekola, ; van Diggelen et al., ; Jímenez‐Alfaro et al., ; Seer and Schrautzer, ; Duval and Waddington, ; Horsáková et al., ). Such fens often show internal patterning, with short, sparse, species‐rich vegetation near springheads grading into taller, denser, less diverse vegetation on less calcareous substrates (Boyer and Wheeler, ; Carpenter, ; Bowles et al., ).…”
mentioning
confidence: 99%
“…Their importance for the conservation of the biodiversity of the region and the country is significant because of the participation of species that are deemed to be endangered in the country as well as the abundance of Liparis loeselii -a species that is of European importance [23], especially because the natural swamp communities in the Silesian Upland are very rare and endangered vegetation components. The particular importance of Ca 2+ and pH is highlighted for the communities of alkaline swamps [31]. Communities that include Liparis loeselii and other calciphilic species that have been found by the Rospuda River grow on a substrate where the water has the following parameters: pH -7.0, conductivity -466 (max 694), Mg +2 -15.9, Ca +2 -21.7 [32].…”
Section: Discussion Of Resultsmentioning
confidence: 99%